Gender Difference in Electroencephalographic and Anxiety Status in Response to Single Bout of Physical Exercise (Health Renaissance, 2011)
Background: Short-term or long-term physical exercise is associated with reductions in anxiety. Cerebral lateralization hypothesis predicts that anxiety reductions caused by exercise is due to decrease in right, relative to left, hemisphere activation. However, research reports on difference in anxiety reduction in response to short-term exercise are scanty. Objective: This study was aimed to compare the effect of acute bout of aerobic exercise on electroencephalographic (EEG) frontal alpha activity and anxiety between genders, and correlate between them. Method: A cross-sectional study was conducted on healthy 30 adult (male=15, female=15) subjects. They bicycled on automated ergometer, maintaining 50% HRmax for 20 min. EEG was recorded from frontal and occipital region (Fp, F1, F2, O1, and O2) and anxiety-scores were recorded before and after exercise. Results: Frontal EEG alpha activity power was significantly greater in females (p